2023
DOI: 10.1002/anie.202215689
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Assisted Halogen Bonding in an Ionic Cavity of a Coordination Cage Based on a Copper(I) Iodide Cluster

Abstract: The design of molecular containers capable of selectively binding specific guest molecules presents an interesting synthetic challenge in supramolecular chemistry. Here, we report the synthesis and structure of a coordination cage assembled from Cu 3 I 4 À clusters and tripodal cationic N-donor ligands. Owing to the localized permanent charges in the ligand core the cage binds iodide anions in specific regions within the cage through ionic interactions. This allows the selective binding of bromomethanes as sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In addition, the formation of solvated C1 with the molecular formula of [(Cu 5 I 8 ) 3– ]­( L 1 ) 3+ was further demonstrated by ESI-MS in the methanol/dimethyl sulfoxide solution, which is depicted in Figure S8. The relative mass-to-charge ratio ( m / z ) peaks at 1348.88, 1506.37, 1593.43, and 1741.48 correspond to the solvated molecular fragments of [ L 1 + Cu 3 I 3 + OH ̅ + Br ̅ + CH 3 OH] + , [ L 1 + Cu 4 I 4 + OH ̅ + Br ̅ ] + , [ L 1 + Cu 4 I 4 + 2OH ̅ + 2CH 3 CH 2 OCH 2 CH 3 ] + , and [ L 1 + Cu 5 I 5 + 2OH ̅ + CH 3 OH + CH 3 CH 2 OCH 2 CH 3 ] + cationic molecular peaks, respectively, which were consistent with the theoretical results. Conclusively, these analysis results indicated that the [(Cu 5 I 8 ) 3– ]-type anionic cluster C1 partially dissembled into cluster fragments in solution, verified by SCXRD (Figures S7 and S8). The cuprous iodide cluster C1 was also identified by X-ray photoelectronic spectrum (XPS) measurements, and the characteristic peaks of Cu 2p were found at 932.15 and 952.0 eV, suggesting that the oxidation state of the copper center was +1 in the anionic cluster (Figure S12).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the formation of solvated C1 with the molecular formula of [(Cu 5 I 8 ) 3– ]­( L 1 ) 3+ was further demonstrated by ESI-MS in the methanol/dimethyl sulfoxide solution, which is depicted in Figure S8. The relative mass-to-charge ratio ( m / z ) peaks at 1348.88, 1506.37, 1593.43, and 1741.48 correspond to the solvated molecular fragments of [ L 1 + Cu 3 I 3 + OH ̅ + Br ̅ + CH 3 OH] + , [ L 1 + Cu 4 I 4 + OH ̅ + Br ̅ ] + , [ L 1 + Cu 4 I 4 + 2OH ̅ + 2CH 3 CH 2 OCH 2 CH 3 ] + , and [ L 1 + Cu 5 I 5 + 2OH ̅ + CH 3 OH + CH 3 CH 2 OCH 2 CH 3 ] + cationic molecular peaks, respectively, which were consistent with the theoretical results. Conclusively, these analysis results indicated that the [(Cu 5 I 8 ) 3– ]-type anionic cluster C1 partially dissembled into cluster fragments in solution, verified by SCXRD (Figures S7 and S8). The cuprous iodide cluster C1 was also identified by X-ray photoelectronic spectrum (XPS) measurements, and the characteristic peaks of Cu 2p were found at 932.15 and 952.0 eV, suggesting that the oxidation state of the copper center was +1 in the anionic cluster (Figure S12).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The UV–vis absorption spectrum of cuprous iodide supramolecular cluster C1 was measured in the solid state and solution. As presented in Table S3 and Figures S15–S20, cluster C1 exhibited a broad absorption band ranging from 235 to 320 nm and a weak peak was found at 420 nm in the solid-state electron absorption spectrum, which were tentatively assigned to the n–π* mixed with π–π* electronic transitions in an organic ligand (ILCT) and metal-to-ligand charge transfer (MLCT), respectively. In the acetonitrile solution of cluster C1 ( c = 1 × 10 –5 mol L –1 , 298 K), an intense absorption band appeared at 286 nm (ε = 24 590 M –1 cm –1 ) and a lower energy band can be observed at 369 nm (ε = 2820 M –1 cm –1 ). Based on previously reported cuprous iodide complexes, in comparison with free organic ligand L 1 , these electron absorption bands possibly originated from the mixed ILCT with MLCT. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the latter, the halogen bond acceptor has to be negatively charged, and hence it is known as charge-assisted halogen bond. 12,[24][25][26] These interactions may be represented as C-Y⋯X-M where M = metal cation. These halogen bonding interactions are known as halogen⋯halogen contacts, where both halogen bond donor and acceptor are halogen atoms.…”
Section: Introductionmentioning
confidence: 99%